MEASURING THE FISCAL PULSE: AN ANALYSIS OF LOCAL GOVERNMENT FINANCIAL HEALTH IN THE ERA OF ECONOMIC RECOVERY - Dewi, Nyoman Ayu Wulan Trisna; I Gd Nandra Hary Wiguna (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Fiscal health refers to the financial condition of a regional government that reflects its ability to manage revenue, expenditure, debt, and deficits in a sustainable manner. Fiscal health plays a crucial role in ensuring the continuity of development and the well-being of the community. Capital expenditure refers to government spending on long-term investments. Effectively allocated capital expenditure can be a key driver of regional development. However, the capital expenditure allocation of Bali Province from 2022 to 2025 has shown fluctuating amounts and tends to be lower compared to other types of expenditures. Good fiscal health enables a region to optimally allocate capital expenditures, thereby impacting sustainable development and community welfare. One of the challenges faced by the government is understanding their fiscal health, especially with increasing public service demands, while their ability to generate own-source revenue remains limited. Based on these conditions, it is necessary to analyze the fiscal health of local governments in Bali Province. This study aims to analyze the fiscal health of local governments based on indicators focused on four main aspects of fiscal health: revenue, expenditure, operating position, and debt structure. The study uses a quantitative descriptive research method. The population in this study consists of the financial reports of the Regency/Municipal Governments throughout Bali Province. The research findings show that the level of fiscal health between regencies/cities in Bali Province in 2022-2023 shows significant disparities. Badung Regency occupies the highest position followed by Gianyar, Bangli, and Denpasar regencies. Badung Regency falls into the high category of fiscal health; Gianyar Regency and Bangli Regency are in the medium category; while Klungkung Regency has improved to the medium category. These findings can provide recommendations for efficient regional financial management strategies to maintain a balance between fiscal health and regional expenditure.